Antidrug antibodies (ADAb) to tumour necrosis factor (TNF)-specific neutralising agents in chronic inflammatory diseases: a real issue, a clinical perspective. Issue 2 (24th November 2012) - Vincent, Fabien B; Morand, Eric F; Murphy, Kim; Mackay, Fabienne; Mariette, Xavier; Marcelli, Christian
Abstract : The introduction of biologics, especially tumour necrosis factor (TNF) inhibitors, has revolutionized the management of chronic inflammatory diseases. However, at least one third of patients with these diseases, receiving TNF inhibitors either do not respond to treatment, or lose initial responsiveness. For a significant proportion, improvement of clinical response is achieved after switching to another anti-TNF drug, suggesting a basis for failure unrelated to the therapeutic target itself. A likely explanation for this is immunogenicity, as all biologics are potentially immunogenic, and the resulting anti-drug antibodies (ADAb) can theoretically decrease the efficacy of biologics and/or induce adverse events. Indeed, in these chronic inflammatory diseases, many studies have now established correlations between ADAb formation, low serum drug levels, and the failure or loss of response to anti-TNF antibodies. This article will review key findings related to ADAb, and propose a model wherein monitoring of drug levels and ADAb may be a predictive tool leading to a better choice of biologics. Such an approach could improve chronic inflammatory disease management toward a personalized and more cost-effective approach.